Kinetics and mechanisms of the reactions of alkyl radicals with oxygen and with complexes of Co(III), Ru(III), and Ni(III) - Kelley, Douglas (Ames Laboratory, 1990)
The kinetics of the reactions of Csub 2Hsub 5 radical with Co(NHsub 3)sub 5X{sup 2+}, Ru(NHsub 3)sub 5X{sup 2+}, and Co(dmgH){sub 2} (X) (Y) (X = Br, Cl, Nsub 3, SCN; Y = Hsub 2O, CHsub 3CN) complexes were studied using laser flash photolysis of ethylcobalt complexes. The kinetics were obtained by the kinetic probe method. Some relative rate constants were also determined by a competition method based on ethyl halide product ratios. The kinetics of colligation reactions of a series of alkyl radicals with {beta}-Ni(cyclam){sup 2+} were studied using flaser flash photolysis of alkylcobalt complexes. Again, the kinetics were obtained by employing the kinetic probe competition method. The kinetics of the unimolecular homolysis of a series of RNi(cyclam)Hsub 2O{sup 2+} were studied. Activation parameters were obtained for the unimolecular homolysis of Csub 2Hsub 5Ni(cyclam)Hsub 2O{sup 2+}. Kinetic and thermodynamic data obtained from these reactions were compared with those for the {sigma}-bonded organometallic complexes. The kinetics of the unimolecular homolysis of a series of RNi(cyclam)Hsub 2O{sup 2+} complexes were studied by monitoring the formation of the oxygen insertion product ROsub 2Ni(cyclam)Hsub 2O{sup 2+}. The higher rate constants for the reactions of alkyl radicals with oxygen in solution, as compared with those measured in the gas phase, were discussed. 30 refs.